ПОСТИНДУСТРИАЛДЫҚ - АҚПАРАТТЫҚ ҚОҒАМДАҒЫ АДАМ ФАКТОРЫНЫҢ РӨЛІ - Нұрсейтова, Г. Б.; Оспанбаев, Ж. А. (Journal of Economic Research & Business Administration, 2016)
Emergence and development of postindustrial society and new economy were discussed in this article. The authors attempted to identify and specify the place and role human factors in postindustrial-information society.